The Correlation of Spiritual Status and Anxiety Level in Patients with Pulmonary Tuberculosis - Merina Widyastuti; Puji Hastuti; Sukma Ayu Candra Kirana; Nevinda Hervi Farendita (Universitas Airlangga, 2020)
Introduction: Pulmonary tuberculosis (TB) is an infectious disease caused by the mycobacterium tuberculosis. The increasing prevalence of tuberculosis and infectious disease overall is causing patients to experience anxiety. Someone who experiences anxiety will find support in their religious beliefs. The purpose of this research was to analyze the relationship between spirituality and the anxiety level of patients with pulmonary tuberculosis.Methods: The study design was analytical observational research with a cross-sectional approach. The independent variable was spirituality and the dependent variable was anxiety. The population of this research was 55 people with pulmonary tuberculosis. The sample totaled 49 people. The retrieval of the data was conducted on 1-31 May 2018 using the Simple Sampling Random technique. The research instrument used the anxiety questionnaire DASS 21 and spiritual questionnaire DSES and the results were tested using Spearman Rho CorrelationsResults: The statistical results with ρ = 0.01 with ρ ≤ 0.05. The results of this study show that the majority of the anxiety levels experienced are normal and that the spiritual outcomes for the majority are at a high level. This shows the relationship between the anxiety level and the spirituality of the patients with pulmonary tuberculosis at Puskesmas Perak Timur Surabaya.Conclusion: The result of the correlation coefficient was 0.552. The implication that the research indicates is that high spiritual intelligence causes someone to reduce their anxiety. Expected health workers can provide more education about the treatment o further reduce the anxiety levels of pulmonary tuberculosis patients.